1999
DOI: 10.1103/physrevb.60.13099
|View full text |Cite
|
Sign up to set email alerts
|

Vortex liquid entanglement in twinnedYBa2Cu3O7

Abstract: The angular dependence of the in-plane resistivity (T,H,) of melt textured YBa 2 Cu 3 O 7 /Y 2 BaCuO 5 composites has been measured in a large range of magnetic fields and temperatures and from them, the intrinsic anisotropy of the superconducting state has been verified following the anisotropic Ginzburg-Landau approach. The influence of correlated defects like twin boundaries and quenched disorder generated by Y 2 BaCuO 5 precipitates on the pinning behavior of these composites in the liquid vortex state is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
15
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 46 publications
1
15
1
Order By: Relevance
“…4,6,10 It was suggested that H lcp was not modified by twin boundaries but this is an unexpected behavior because twin boundaries lead to a secondorder Bose-glass transition, 11 characterized by a cusp in the ''irreversibility line'' and in the vortex activation energy for magnetic-field orientations close to the c axis. 12,13 This behavior would be also inconsistent with a recent study of the influence on H lcp of linear defects created by ion irradiation. 8 That work showed that H lcp is pushed up while the Boseglass regime develops.…”
contrasting
confidence: 48%
“…4,6,10 It was suggested that H lcp was not modified by twin boundaries but this is an unexpected behavior because twin boundaries lead to a secondorder Bose-glass transition, 11 characterized by a cusp in the ''irreversibility line'' and in the vortex activation energy for magnetic-field orientations close to the c axis. 12,13 This behavior would be also inconsistent with a recent study of the influence on H lcp of linear defects created by ion irradiation. 8 That work showed that H lcp is pushed up while the Boseglass regime develops.…”
contrasting
confidence: 48%
“…These results have allowed us to identify a partially entangled vortex liquid phase in YBa 2 Cu 3 O 7 , when quenched and correlated disorders compete. The main characteristic of this new phase, which was qualitatively claimed in [12,13], is a finite c-axis vortex correlation length. Y123͞211 composites were grown by a modified Bridgman method [10].…”
mentioning
confidence: 57%
“…The activation energy of the form of U pl , is then a strong indication of vortex entanglement. 30,31,34 Since vortex entanglement involves vortex deformations of size a 0 , and melting involves deformations which are a fraction c L ͑the Lindemann number͒ of the vortex lattice spacing, the basic energy scale governing vortex entanglement (U pl ϳ␥ Ϫ1 ⑀ 0 a 0 ) is the same governing melting. Plastic barriers and melting temperature, T g , can be related via the Lindemann number:…”
mentioning
confidence: 99%
“…Additionally, we would like to remark that, besides correlated disorder, there is, most likely, also point disorder present in the nonirradiated samples, and there may be then a complicated interplay between both types of defects. 10,34 In summary, we have studied the effect of light ion irradiation on the dissipation properties of epitaxial YBCO films. The dynamics of the vortex solid to liquid transition seems not to be modified by ion irradiation.…”
mentioning
confidence: 99%